Cooking for jeffrey ebook A barefoot contessa cookbook. - Garten, Ina (2016)
For America’s bestselling cookbook author Ina Garten there is no greater pleasure than cooking for the people she loves—and particularly for her husband, Jeffrey. She has been cooking for him ever since they were married forty-eight years ago, and the comforting, delicious meals they shared became the basis for her extraordinary career in food.   Ina’s most personal cookbook yet, Cooking for Jeffrey is filled with the recipes Jeffrey and their friends request most often as well as charming stories from Ina and Jeffrey’s many years together. There are traditional dishes that she’s updated, such as Brisket with Onions and Leeks, and Tsimmes, a vegetable stew with carrots, butternut squash, sweet potatoes, and prunes, and new favorites, like Skillet-Roasted Lemon Chicken and Roasted Salmon Tacos. You’ll also find wonderful new salads, including Maple-Roasted Carrot Salad and Kale Salad with Pancetta and Pecorino. Desserts range from simple Apple Pie Bars to showstoppers like Vanilla Rum Panna Cotta with Salted Caramel. For the first time, Ina has included a chapter devoted to bread and cheese, with recipes and tips for creating the perfect cheese course. With options like Fig and Goat Cheese Bruschettas and Challah with Saffron, there’s something everyone will enjoy. From satisfying lunches to elegant dinners, here are the recipes Ina has tested over and over again, so you too can serve them with confidence to the people you love.